Correlaciones entre la morfología de nebulosas planetarias y el tipo espectral de sus estrellas centrales - Mudrik, Armando (2022)
The mechanisms by which an ordinary star gives rise to a planetary nebula (PN) remain uncertain. The reason why central stars of PNe have both hydrogen-rich and hydrogen-poor atmospheres is also unknown. Certainly the mechanisms that trigger mass loss are related to the hydrogen abundance of the remnant star. On the other hand, the morphology displayed by PNe is necessarily related to the mass-loss mechanism. We have found that the hydrogen abundance in the central stars of PNe atmosphere does not correlate with PN morphology. We also show that a similar distribution of morphologies is observed for different evolutionary stages of CSPNe, suggesting that morphology does not change with PN age. Finally we present evidence suggesting that binary cores do not correlate with NPe of bipolar morphology.